Platelet Aggregation Before Aspirin Initiation in Pediatric Patients With Congenital Heart Disease at High Risk of Thrombosis - Lu, Zhong-Yuan; Zhu, Zhi-Yuan; Yang, Ju-Xian; Zhou, Yu-Zi; Jiang, Ya-Zhou; Wei, Wei; Wang, Xu; Li, Shou-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background. The sequential anticoagulation treatment that aspirin following unfractionated heparin is the most common strategy for pediatric patients at high risk of thrombosis after cardiac surgery. However, the platelet aggregation status before postoperative aspirin initiation and the related clinical influencing factors hasn’t been investigated systemically in this population. METHODS：In 247 children, arachidonic acid induced platelet aggregation (PAG-AA) was measured by means of light transmission aggregometry (LTA) before the first dose of aspirin and the perioperative variables were also documented in this prospective observational study. Univariate and multivariate logistic regression analysis were performed to identify the main influencing factors. RESULTS：The median time of aspirin administration was 2 days after surgery and the corresponding basal PAG-AA was 20.70% (1.28%-86.49%), with 67.6% distributed under 55% and 47.8% under 20%. Patients undergoing cardiopulmonary bypass (CPB) had a significantly lower basal PAG-AA than those without (30.63±27.35 VS 57.91±27.58, P=0.013). While aspirin initiation (test done) within 3 days after CPB had a significant lower PAG-AA than those initiated out of 3 days (25.61±25.59 VS 48.59±26.45, P=0.001). Univariate analysis showed that the influencing factors of basal PAG-AA including CPB, time of aspirin initiation, cyanosis and platelet count, but multivariate regression analysis showed that only CPB and the time of aspirin initiation were the main independent influencing factors for the basal PAG-AA and the others were not. Conclusion: In the current sequential anticoagulation treatment that aspirin following unfractionated heparin for pediatric patients at high risk of thrombosis after cardiac surgery, the basal PAG-AA values that tested before aspirin initiation fluctuated widely, with mostly below the normal range and even in severely low state. The main influencing factors are cardiopulmonary bypass and the time of aspirin initiation. The basal PAG-AA is significantly lower when surgery undergoing with CPB and also when aspirin initiated within 3 days after CPB. The duration of CPB and cyanosis seems had no significant impact on the basal value. To accurately evaluate the effect of aspirin, PAG-AA testing should be performed after the impairment of cardiopulmonary bypass is basically over，3 days out may better.